Pendampingan Penyusunan Media Informasi Pariwisata di Museum Kretek dengan Penerapan Bilingual Method - Rismiyanto Rismiyanto; Fitri Budi Suryani; Muh Syafei (Universitas Muria Kudus, 2023)
Kudus has good industrial and tourism potential. One of them is the cigarette industry; and even because there are so many cigarette industries there, Kudus Regency government built Kretek Museum as a tourist media as well as the one for preserving the history of the cigarette industry that can attract tourists from all over the world. This potential has not been realized optimally, because the tourist information media at Kretek Museum still only uses Indonesian. This community service activity aims to provide assistance to the Kretek Museum in completing tourism information media using bilingual method combining Indonesian and English. This service activity is carried out through a review, revision and addition, and the preparation of tourism information media with the bilingual method. Through Assistance in the Preparation of Tourism Information Media with the Application of the Bilingual Method, tourist information media at the Kretek Museum can be accessed more effectively by tourists from all over the world.